2020
DOI: 10.1186/s12993-020-00167-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression is associated with altered functional connectivity between neural circuits related to visual, auditory, and cognitive processing during stories listening in preschoolers

Abstract: Background: Maternal depression can influence the early activity of a mother reading stories to a young child, as depressed mothers are less likely to read to their children. Here, maternal depression association to neurobiological circuitry of narrative comprehension, visualization, and executive functions during stories listening was examined in 21 4-year-old girls and their mothers. Maternal depression scores were collected from the mothers, and functional MRI during stories listening was collected from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Maternal responsiveness training facilitates greater growth in social, emotional, communication, and cognitive skills of 6‐ to 13‐month‐old infants (Landry et al, 2006), promotes expressive language skills, social engagement, and complex toy play in 30‐month‐old toddlers (Guttentag et al, 2014), and improves language and communication skills in children under 6 (Roberts et al, 2019). Finally, reduced maternal responsiveness or nonresponsiveness (in circumstances such as postnatal depression or family adversity) is related to cognitive deficits (Milgrom et al, 2004), lower school readiness, language skills, and cooperativeness (NICHD Early Child Care Research Network, 1999), and altered brain development (Farah et al, 2020) in toddlers and preschoolers, increased risk of disruptive behavior problems in middle childhood (Wakschlag & Hans, 1999), and poorer academic performance in adolescence (Murray et al, 2010).…”
Section: Mother–child Interaction and Child Developmentmentioning
confidence: 99%
“…Maternal responsiveness training facilitates greater growth in social, emotional, communication, and cognitive skills of 6‐ to 13‐month‐old infants (Landry et al, 2006), promotes expressive language skills, social engagement, and complex toy play in 30‐month‐old toddlers (Guttentag et al, 2014), and improves language and communication skills in children under 6 (Roberts et al, 2019). Finally, reduced maternal responsiveness or nonresponsiveness (in circumstances such as postnatal depression or family adversity) is related to cognitive deficits (Milgrom et al, 2004), lower school readiness, language skills, and cooperativeness (NICHD Early Child Care Research Network, 1999), and altered brain development (Farah et al, 2020) in toddlers and preschoolers, increased risk of disruptive behavior problems in middle childhood (Wakschlag & Hans, 1999), and poorer academic performance in adolescence (Murray et al, 2010).…”
Section: Mother–child Interaction and Child Developmentmentioning
confidence: 99%
“…The cuneus is part of the occipital lobe and is involved in visual perception functions (e.g., facial emotion) and plays an important role in social interaction (58,59). Functional changes in the cuneus lobe are also closely related to MDD (60,61). A study of an fMRI reward processing task found that adolescents with unremitting depression showed greater activation in the frontal middle gyrus and less activation in the cuneus compared to adolescents with remitting depression (62).…”
Section: Discussionmentioning
confidence: 99%
“…21 Indirect mechanisms include disrupted home and/or school routines by frequent medical appointments, disease flares, and/or prolonged hospital stays, particularly during early childhood. [28][29][30][31] Extended time in the hospital and family stress 32 may also negatively affect HLE via displaced shared reading time and/or competing priorities (i.e., diminished importance relative to physical health, rehabilitation and survival). Children with chronic illness are also prone to high levels of screen use, as they are more often sick and/or isolated at home or in the hospital.…”
Section: Introductionmentioning
confidence: 99%